Detection of Hepatitis B Virus Genotypes F and G associated with liver disease in tertiary hospital / Nabilah Mohd Noor - Mohd Noor, Nabilah (2015)
Hepatitis B virus infection can trigger development of liver disease from acute to chronic hepatitis. Hepatitis B virus genotype is one of the factors that contribute to development of HBV-liver related disease. Ten HBV genotypes have been found which are genotype A through genotype J, with genotype Band C are predominant genotypes in Malaysia. This study was done to identify the hepatitis B genotype F and genotype G in patients with liver disease in a tertiary hospital, and describe the correlation of demographic data as risk factors for hepatitis B virus infection and liver disease. Realtime PCR assay was used in this study to detect presence of HBV genotype F and G in 35 HBV positive serum samples obtained from Kuala Lumpur General Hospital. Among 35 HBV positive samples, 13 samples were positive for genotype F, five samples were positive genotype G, eight samples were positive genotype F and q. Twenty males and 15 females were infected by HBV. In term of ethnic compositions, 17 were Chinese, 11 Malay, one Indian and six from others ethnics in Malaysia. Samples according to age groups, showed the highest infection case reported among patients age between 41 to 60 with frequency 16 out of 35 patients. In conclusion, hepatitis B genotype F was the highest genotype that detected among patient liver disease in tertiary hospital compared to genotype G. This study gives a new insight for the presence of other genotype of HBV among Malaysian. Further investigation should be done with more specific and sensitive method.